PENGARUH KEPERCAYAAN MEREK TERHADAP LOYALITAS MEREK PADA PRODUK MINUMAN YOU C 1000mg : Survei Pada SPG Pengguna Minuman Bervitamin YOU C 1000mg di Carrefour PVJ Sukajadi - Acep Hermawan, - (2010)
Indonesia has been affected by the global crisis that happens in almost all countries in entire world. The crisis even strike to and begin from known as a superpower country with properly economic capability, is a failure of global capitalism system. The impact made the marketers did special strategies in order to be able to solve the competitor's threat and strengthen the excelently competition in the condition of global crisis nowdays, especially the companies which is operated in drink industry. The company must be able to sustain the custumer. One of the ways is to arouse the trust of brand toward the resulted brand that will create the loyalty towards the brand. This research is aimed to study empirically the influence of brand trust variable which includes brand characteristic, company characteristic and consumer - brand characteristic to brand loyalty. The mark being researched is drink Vitamin You C1000mg of which respondents are take from SPG Carrefour the use of You C1000 Vitamin drink. The result of this research shows that simultaneous and partial variable of brand trust have significant effect to brand loyalty. The effect of brand trust to brand loyalty is 0.775 with significance level of 0.000. While partially, the effect of brand trust variable is as follows: first, the brand characteristic has significant effect to brand loyalty with beta coefficient of 0.586 with significance level of 0.000, where brand characteristic has dominant effect to brand loyalty. The company characteristic has significant effect to brand loyalty with beta coefficient of 0.246 with significance level of 0.000. Consumer - brand characteristic also has significant to brand loyalty with beta coefficient of 0.256 with significance level of 0.000. In the effort to increase loyalty to brand, the company must increase and maintain trust of customers to the company. Brand characteristic is as one of the most dominant variable must remain to be controlled directly by the company.